Characterization and osteogenic evaluation of mesoporous magnesium–calcium silicate/polycaprolactone/polybutylene succinate composite scaffolds fabricated by rapid prototyping. Issue 59 (2nd October 2018) - Kang, Yun Gyeong; Wei, Jie; Kim, Ji Eun; Wu, Yan Ru; Lee, Eun Jin; Su, Jiacan; Shin, Jung-Woog
Abstract : A new composite scaffold consisting of mesoporous magnesium–calcium silicate (m_MCS), polycaprolactone (PCL), and polybutylene succinate (PBSu) was manufactured by a rapid prototyping technique, for stem cell-based bone tissue engineering. Abstract : The properties of scaffolds for bone tissue engineering, including their biocompatibility, highly interconnected porosity, and mechanical integrity, are critical for promoting cell adhesion, proliferation, and osteoinduction. We used various physical and biological assays to obtain in vitro confirmation that the proposed composite scaffolds are potentially suitable for applications to bone tissue engineering. The proposed new composite scaffolds, which we fabricated by a rapid prototyping technique, were composed of mesoporous magnesium–calcium silicate (m_MCS), polycaprolactone (PCL), and polybutylene succinate (PBSu). We systematically evaluated the characteristics of the composite scaffolds, such as the hydrophilicity and bioactivity. We also investigated the proliferation and osteogenic differentiation of human mesenchymal stem cells (MSCs) scaffolded on the m_MCS/PCL/PBSu composite. Our results showed that, compared to the m_MCS/PCL scaffold, the m_MCS/PCL/PBSu scaffold has improved water absorption, in vitro degradability, biocompatibility, and bioactivity in simulated body fluid, while its mechanical strength is reduced. Moreover, the results of the cytotoxicity tests specified in ISO 10993-12 and ISO 10993-5 clearly indicate that the m_MCS/PCL scaffold is not toxic to cells. In addition, we obtained significant increases in initial cell attachment and improvements to the osteogenic MSC differentiation by replacing the m_MCS/PCL scaffold with the m_MCS/PCL/PBSu scaffold. Our results indicate that the m_MCS/PCL/PBSu scaffold achieves enhanced bioactivity, degradability, cytocompatibility, and osteogenesis. As such, this scaffold is a potentially promising candidate for use in stem cell-based bone tissue engineering.